Trinidad and Tobago. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the Trinidad and Tobago Delegation of 2022 are identified, focus to needs and interests of the country such as; conduct strategic disease surveillance and diagnostics, as well as deliver rapid responses to protect livestock from animal diseases; supported officials in networking and improving their knowledge to address current and emerging pests and diseases that threaten productivity, yields, farm incomes and exports; facilitated technical expertise and networking; targeted training through online and face-to-face workshops on food safety from farm to market, climate vulnerabilities and make decisions to build their climate resilience, related to the need to measure and report data on greenhouse gas (GHG) emissions, including from agriculture; also supported business networking, training, troubleshooting, market exposure and support for product quality enhancement via WhatsApp, virtual webinars and face-to-face sessions.